Inflammatory low back pain: diagnostic and therapeutical recommendations for family doctors - Kucharz, Eugeniusz Józef; Mastalerz-Migas, Agnieszka; Kwiatkowska, Brygida; Gasik, Robert; Kotulska, Anna; Kowalczewski, Jacek; Tomasik, Tomasz (Family Medicine & Primary Care Review, 2016)
Low back pain (LBP) or pain of the lumbo-sacral region of the vertebral column is a polyetiological clinical state. LBP is a common medical condition and has a recurrent nature. The incidence of the first LBP episode in life varies from 6.3 to 15.4% a year, while the total annual LBP incidence is estimated at up to 36%. The cause of LBP can be located in the osseous structures and the joints of the vertebral column, the intervertebral discs, as well as the muscles, ligaments and nerves of the lumbo-sacral region. Commonly, the disease mechanism is complex. Differential diagnosis is an important part of the management of LBP patients due to a number of potential causes. Some forms of LBP need emergency management, and their features are known as “red flag symptoms”. Such LBP forms occur at night and lack any connection with physical activity (especially in the early stage of the disease). Rapidly deteriorating LBP also needs to be considered as an emergency. Inflammatory LBP occurs in patients with inflammatory spondyloarthropathies (in 70–80% of the patients). The presented recommendations are designed to facilitate the identification of patients with inflammatory LBP. They also describe rules of referring to a rheumatologist, as well as focus on the cooperation of a family doctor and a rheumatologist in the treatment of these patients. In most patients LBP is the first symptom of inflammatory spondyloartropathy. The classification criteria of inflammatory LBP are as follows: 1) onset at the age below 40; 2) insidious onset; 3) an improvement after physical exercise; 4) the lack of improvement after rest; 5) pain at night with improvement after getting up from bed. Non-pharmacological (kinesiotherapy, patient education) and pharmacological methods (non-steroidal anti-inflammatory drugs, TNF -alpha blockers) are used in the management of patients with inflammatory spondyloartropathy.